Integrated Yoga and Ayurveda therapy for negative symptoms in schizophrenia: A case series highlighting safety and synergistic value of integrative and personalized healthcare - Kavyashree Kulamarva; Varsha Karanth; Chandrasena Santosh; Chikkanna Umesh; Hemant Bhargav; Venkataram Shivakumar; Kishore Kumar Ramakrishna; Nishitha Jasti; Shivarama Varambally (Journal of Ayurveda and Integrative Medicine, 2025)
Negative symptoms are a significant contributor to the psychopathology of schizophrenia, primarily affecting socio-occupational functioning. Though effective in managing positive symptoms, most pharmacological agents have limited effects on the negative symptoms of schizophrenia, especially the primary negative symptoms. We discuss five cases (4 males, one female, age range: 24–36 years) of chronic schizophrenia (diagnosed as per ICD-10 criteria) with duration of illness ranging from 2 to 18 years. All the cases had negative symptoms with moderate to extreme severity on the scale for assessment of negative symptoms (SANS) (scores 49 or above; range 49–82). Subjects underwent integrated yoga and ayurveda (IYA) intervention for 12 weeks. Ayurveda intervention included systematic detox (Panchakarma Shodhana) and pacifying herbs (Shamana), whereas yoga involved the practice of a previously validated yoga module. For all the subjects, anti-psychotic medications were stable for the last eight weeks and did not change during the 12-week IYA intervention and eight weeks after. Post-intervention SANS scores were reduced in all the subjects. The reduction of SANS scores ranged from −15 to −43 (average: −35.6), corresponding to CGI-I ratings of ‘much improved’ in three subjects and ‘minimally improved’ in two subjects. Clinical assessments by an independent psychiatrist at baseline, during IYA (4 weeks), immediately post-IYA (12 weeks), and eight weeks post-IYA did not reveal any new potential side effects due to IYA or worsening of other clinical symptoms or exaggeration of side effects of antipsychotics. This needs further scientific exploration through systematic clinical and mechanistic trials in the future.